The impact of COVID-19 safety interventions on creating a controlled environment on campus - Mahmood, Sana; Ijaz Haider, Sonia; Shahbaz, Hamna; Noorali, Ali Aahil; Afzal, Noreen; Jiwani, Aziz; Zaki, Samar; Iqbal Khan, Unab; Ajani, Khairulnissa; Tariq, Muhammad; Karmaliani, Rozina; Haider, Adil Hussain (Frontiers in Public Health, 2022)
Objectives During COVID-19 the re-opening of educational institutes was frequently debated, however with the decline in the number of COVID-19 cases, The Aga Khan University (AKU) in Karachi, Pakistan opened its campus for medical and nursing students after more than 6 months of closure. To ensure gradual resumption of activities on-campus, a combination of interventions was diligently deployed to minimize student infection rates. Scarce literature exists on students’ perceptions regarding decisions implemented by university leadership. The aim of the study was to determine the efficacy of these interventions. Methods We conducted a convergent, parallel, mixed-methods observational study targeting medical and nursing students. An online questionnaire was disseminated to elicit students’ degree of (dis)agreement on a four-point Likert scale. Focused group discussions (FGDs) were conducted to comprehend reasons for (dis)agreement. Results Total of 183 students responded to questionnaire (59.0% nursing, 67.8% female), 11 FGDs were conducted with 85 students. Interventions with highest agreement were mandatory face masks policy (94.54%), weekly mandated COVID-testing (92.35%) and students’ Academic Bubble (91.26%); highest disagreement was for Sehat Check application (41.53%) and stay strong campaign (40.44%). Four themes emerged from FGDs: Effective safety interventions, Safety interventions with limited effectiveness, Utility of Sehat Check Application and Future recommendations for informing policy. Conclusion It is paramount to seek student-feedback at forefront of university re-opening strategy. Clear communication channels are as important as an administrative response system’s robustness. Bidirectional communication channels are fundamental and requisite during ever-changing policies and regulations. Engaging student representatives in decision making or implementation processes (such as ‘pilot’ before ‘roll-out’) would allow any potential issues to be managed early on. Gather real-time anonymous feedback and identify key areas that need further promulgation and those that need to be replaced with more effective ones.